The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1021/jacs.3c07445
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon Degradation by Contact with Anoxic Water Microdroplets

Xuke Chen,
Yu Xia,
Zhenyuan Zhang
et al.

Abstract: Oils are hydrophobic, but their degradation is frequently found to be accelerated in the presence of water microdroplets. The direct chemical consequences of water−oil contact have long been overlooked. We show that aqueous microdroplets in emulsified water− hexadecane (C 16 H 34 ) mixtures can spontaneously produce CO 2 , •H, H 2 , and short-chain hydrocarbons (mainly C 1 and C 2 ) as detected by gas chromatography, electron paramagnetic resonance spectroscopy, and mass spectrometry. This reaction results fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 60 publications
2
17
0
Order By: Relevance
“…We propose that water is the major source for reducing hydrogen. In previous work, electron spin resonance spectroscopy has shown that hydroxyl radicals ( • OH) and hydrogen atoms ( • H) are formed at the gas–water and solid–water interfaces, which strongly supports the recent proposal that Colussi made for hydrogen peroxide formation on the sprayed water microdroplet surface . Interestingly, the endothermicity of electron transfer in bulk water (Δ H = 448 kJ mol –1 ) is reversed at the water interface by the destabilization of the hydrated reactant ions: Δ H hydration (H + + OH – ) = −1670 kJ mol –1 , relative to neutral radical products: Δ H hydration ( • OH + • H) = −58 kJ mol –1 .…”
Section: Resultssupporting
confidence: 74%
“…We propose that water is the major source for reducing hydrogen. In previous work, electron spin resonance spectroscopy has shown that hydroxyl radicals ( • OH) and hydrogen atoms ( • H) are formed at the gas–water and solid–water interfaces, which strongly supports the recent proposal that Colussi made for hydrogen peroxide formation on the sprayed water microdroplet surface . Interestingly, the endothermicity of electron transfer in bulk water (Δ H = 448 kJ mol –1 ) is reversed at the water interface by the destabilization of the hydrated reactant ions: Δ H hydration (H + + OH – ) = −1670 kJ mol –1 , relative to neutral radical products: Δ H hydration ( • OH + • H) = −58 kJ mol –1 .…”
Section: Resultssupporting
confidence: 74%
“…However, water oxidation forming the peroxide should also yield a product of water reduction. Nguyen et al 129 proposed that hydrogen is the reduced coproduct of hydrogen peroxide formation and asked for its experimental verification that was recently published, 130 analogous to hygroelectricity. 131 A different mechanism proposed by Colussi identifies the mechanical energy required for droplet formation as the energy source for hydrogen peroxide formation.…”
Section: Consequences Of Water Electrificationmentioning
confidence: 99%
“…Notably, recent findings indicate the activation of H 2 O to produce active hydrogen species (H*), promoting CO 2 adsorption and hydrogenation . Zare and Jia et al showed that contact electrification at water–oil microdroplet interfaces in an emulsion initially enabled a spontaneous evolution of H 2 and the accumulation of ROS, leading to the oxidative cracking of oil at ambient temperature . Colussi demonstrated that electron transfer (ET) between surface-bound ions (OH S – + H S + ) at water microdroplet interfaces can produce H S • , which further promotes CO 2 reduction .…”
Section: Introductionmentioning
confidence: 99%